ECO-THEOLOGY AND MINING MANAGEMENT POLICY BY RELIGIOUS ORGANIZATIONS IN INDONESIA: AN ISLAMIC PERSPECTIVE - Muh. Mukhlish Abidin; Umi Farihah Arif (Religi: Jurnal Studi Agama-agama, 2026)
This study aims to analyze the Indonesian government's policy of granting special mining business permits (WIUPK) to religious community organizations (ormas) for their participation in managing mines using an Islamic eco-theology analysis. The granting of these permits has sparked debate from many parties and concerns arise about overlapping economic interests, environmental ethics, and spiritual responsibilities, making this phenomenon interesting to study. This study uses a qualitative-descriptive approach with a literature analysis of religious sources in the form of texts of the Qur'an and hadith, state regulations, and academic literature on eco-theology. Based on the analysis, the results show that Islam teaches the values ​​of balance (mizan), justice (al-'adl), and the value of welfare (istishlah). These principles are highly relevant for mining governance to utilize natural resources without causing damage. Thus, it can be concluded that Islamic eco-theology can serve as a moral and spiritual foundation for mining management by religious organizations so that the implementation of this policy runs according to expectations for the welfare of the community. Islamic eco-theology serves as a guideline for mining activities that can become a field for preaching and social worship, as well as sustainable development that is rahmatan lil-‘alamin. Keyword: Islamic eco-theology, public policy, mining, religious organizations   Penelitian ini bertujuan menganalisis kebijakan pemerintah Indonesia yang memberikan wilayah izin usaha pertambangan khusus (WIUPK) kepada organisasi masyarakat (ormas) keagamaan dalam keikutsertaannya mengelola tambang dengan analisis ekoteologi Islam. Pemberian izin ini sempat menimbulkan perdebatan dari banyak pihak dan dikhawatirkan terjadi tumpang tindih antara kepentingan ekonomi, etika lingkungan, dan tanggung jawab spiritual sehingga fenomena ini menarik untuk dikaji. Penelitian ini menggunakan pendekatan kualitatif-deskriptif dengan analisis kepustakaan terhadap sumber keagamaan berupa teks Al-Qur’an dan hadis, regulasi negara, dan literatur akademik tentang ekoteologi. Berdasarkan analisis, hasil penelitian menunjukkan bahwa Islam mengajarkan nilai-nilai keseimbangan (mizan), nilai keadilan (al-‘adl) dan nilai kemaslahatan (istishlah). Prinsip-prinsip ini sangat relevan bagi tata kelola tambang untuk memanfaatkan sumber daya alam tanpa harus menimbulkan kerusakan. Dengan demikian, dapat disimpulkan bahwa ekoteologi Islam dapat menjadi landasan moral dan spiritual dalam pengelolaan tambang oleh ormas keagamaan agar implementasi kebijakan ini berjalan sesuai harapan untuk kesejahteraan umat. Ekoteologi Islam menjadi pedoman dalam kegiatan tambang yang bisa menjadi ladang dakwah dan ibadah sosial, serta pembangunan berkelanjutan yang rahmatan lil-‘alamin. Kata kunci: ekoteologi Islam, kebijakan publik, tambang, ormas keagamaan